2022
DOI: 10.3389/fpubh.2022.890507
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Insurance, Income Distribution, and Inclusive Growth

Abstract: Financial inclusion, whereby all adults have effective access to financial products, including insurance, has increasingly become a global priority, particularly in low and middle income economies. This study matches the measured development level of inclusive insurance in Chinese provinces with China Family Panel Studies (CFPS) data and evaluates the impact of inclusive insurance on income distribution and inclusive growth. The findings support that inclusive insurance has a positive impact on income distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Firstly, in the case of older individuals, the government should consider introducing CMI-subsidy policies for the elderly, while the insurance industry should expand publicity channels and methods to improve the awareness of CMI among the elderly. It is also necessary to scale up social business integrated medical insurance, a kind of inclusive CMI that is more friendly to the elderly, with the advantages of low cost, simple terms, broad coverage, and easy access [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in the case of older individuals, the government should consider introducing CMI-subsidy policies for the elderly, while the insurance industry should expand publicity channels and methods to improve the awareness of CMI among the elderly. It is also necessary to scale up social business integrated medical insurance, a kind of inclusive CMI that is more friendly to the elderly, with the advantages of low cost, simple terms, broad coverage, and easy access [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study carried out in China showed that inclusive insurance impacts positively income distribution and inclusive growth as well. More than this, such a type of policy strategy is more pronounced in rural and low-income households ( 37 ). Thus, health insurance and social security programs are very important tools not only to reach universal health coverage but also to reduce inequality of different types.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…IMI is characteristic insurance proposed by China to improve the medical insurance system. Most of the existing studies are about the top-level design of its theoretical development [52][53][54]. At present, we found only one empirical study on IMI.…”
Section: Imi Related Workmentioning
confidence: 97%